Functional Surfaces via Laser Processing in Nickel Acetate Solution - Stanciu, Elena Manuela; Pascu, Alexandru; Croitoru, Catalin; Roata, Ionut Claudiu; Cristea, Daniel; Tierean, Mircea Horia; Hulka, Iosif; Petre, Ioana Madalina; Rosca, Julia Claudia Mirza (MATERIALS, 2023)
This study presents a novel laser processing technique in a liquid media to enhance the surface mechanical properties of a material, by thermal impact and micro-alloying at the subsurface level. An aqueous solution of nickel acetate (15% wt.) was used as liquid media for laser processing of C45E steel. A pulsed laser TRUMPH Truepulse 556 coupled to a PRECITEC 200 mm focal length optical system, manipulated by a robotic arm, was employed for the under-liquid micro-processing. The study’s novelty lies in the diffusion of nickel in the C45E steel samples, resulting from the addition of nickel acetate to the liquid media. Micro-alloying and phase transformation were achieved up to a 30 µm depth from the surface. The laser micro-processed surface morphology was analysed using optical and scanning electron microscopy. Energy dispersive spectroscopy and X-ray diffraction were used to determine the chemical composition and structural development, respectively. The microstructure refinement was observed, along with the development of nickel-rich compounds at the subsurface level, contributing to an improvement of the micro and nanoscale hardness and elastic modulus (230 GPa). The laser-treated surface exhibited an enhancement of microhardness from 250 to 660 HV0.03 and an improvement of more than 50% in corrosion rate.
Keywords: laser treatment; microalloying; diffusion; microstructure; liquid media; surface hardening